RANCANG BANGUN APLIKASI INVENTARIS TOKO AMI IT & CREATIVE BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL 9: DESIGN AND BUILD A WEB-BASED AMI IT & CREATIVE STORE INVENTORY APPLICATION USING THE LARAVEL 9 FRAMEWORK - Abdul Malik Mombay; Christian Dwi Suhendra; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2024)
TOKO AMI IT & CREATIVE is a store located at Sp7 Kampung Sumberboga, Masni District. TOKO AMI IT & CREATIVE itself is a business store that runs an office stationery (ATK) and printing business. At this time, many people have problems managing stock inventory, which is one of the most important things for a business field such as a store. If an item is not properly inventoried, it can cause problems such as inconsistency in the stock of available goods, loss of data on goods owned, long search for item data, a lot of time consuming when managing data, and losses. Therefore, this research aims to assist business processes in TOKO AMI IT & CREATIVE in building web-based applications. The system development methods used are the System Development Life Cycle (SDLC) and Prototype, because this development process has the stages needed in its development.